Adipose-derived stem cells extracellular vesicles enhance diabetic wound healing via CCN2/PI3K/AKT pathway: therapeutic potential and mechanistic insights - Yu-lu Zhou; Shingo Ogura; Hao Ma; Rong-bin Liang; Shao-yihan Fang; Yue-ming Wang; Yan Wo; Wen-jin Wang; De-Wu Liu (Stem Cell Research & Therapy)
Abstract Background Adipose-derived stem cells extracellular vesicles (ADSCs-EVs) hold significant promise in tissue repair and regeneration. While they have been reported to enhance diabetic wound healing, the precise mechanisms remain unclear. Methods ADSCs-EVs were isolated via ultracentrifugation and characterized through transmission electron microscopy, Western blot, and nanoparticle tracking analysis. Their effects on human umbilical vein endothelial cells (HUVECs) and RAW 264.7 macrophages were assessed in vitro, focusing on cell proliferation, migration, tube formation, and macrophage polarization. A diabetic rat wound model was used to evaluate their therapeutic impact on wound healing and angiogenesis, with histological and immunofluorescence analyses. mRNA sequencing identified Cellular communication network factor 2(CCN2) as a key upregulated gene, leading to further exploration of its role in ADSCs-EVs-mediated angiogenesis and wound healing via the PI3K/AKT pathway. Gene silencing (si-CCN2) and pharmacological inhibition (LY294002) were employed both in vitro and in vivo. Results ADSCs-EVs were successfully isolated and characterized. In vitro, ADSCs-EVs promoted HUVEC proliferation, migration, and tube formation, and facilitated macrophage polarization to the M2 phenotype. In vivo studies using a diabetic rat wound model confirmed the pro-healing effects of ADSCs-EVs, including enhanced angiogenesis, granulation tissue formation, and accelerated wound closure. mRNA sequencing revealed that CCN2 expression was significantly upregulated in diabetic wound tissues treated with ADSCs-EVs. Further experiments showed that inhibiting CCN2 expression (si-CCN2) or blocking the PI3K/AKT pathway (LY294002) partially suppressed HUVEC proliferation, migration, tube formation, and angiogenesis, and counteracted the pro-healing effects of ADSCs-EVs. Conclusions ADSCs-EVs promote diabetic wound healing through the CCN2/PI3K/AKT pathway, offering a promising therapeutic target for diabetic wound repair.